Distribution Of Information On Independent Waste Management By The Creative Industry Of Tourism Awareness Groups (Pokdarwis) In Kampung Ketupat, Samarinda City As A Potential For Ecotourism Industry Based On Community-Based Research Model - Shorea Helminasari; Shakira Mustafa; Muhammad Edhil Arfan (Journal of Social Research, 2025)
Waste has become a serious global issue experienced by almost all regions of the world, including Indonesia. The prevailing stigma in waste management within society has been that the government handles waste from the source, to temporary disposal sites (TPS), and then to final disposal sites (TPA). Waste management is a major challenge often faced by urban communities, including the city of Samarinda. Samarinda has various destination areas with tourism and economic potential that attract the attention of local residents as well as international visitors. One such place is Kampung Ketupat, a tourism village located in Samarinda Seberang District, Mesjid Subdistrict, specifically in the Mangkupalas Road area. This area is officially managed by the Tourism Awareness Group (Pokdarwis), which reports that some residents still frequently dispose of waste into the river without proper waste disposal management. Kampung Ketupat has great potential to become a sustainable community-based ecotourism area. Strategic steps in distributing information related to independent waste management by involving creative industry players and local communities will not only help reduce environmental impacts but also increase public awareness of the importance of environmental sustainability as a tourism asset. Kampung Ketupat can serve as a model for community-based waste management in line with Samarinda City Regional Regulation Number 5 of 2021 concerning waste management. This activity aims to implement a community-based service model in Kampung Ketupat, Samarinda City, involving Pokdarwis as well as the local government. The activities include training, seminars, public discussions, and community awareness campaigns. Regular evaluations will be conducted to ensure the sustainability and success of this program. It is expected that the residents of Kampung Ketupat, Samarinda City, will be more actively involved in independent waste management and the creative industry as a potential ecotourism industry.